2023
DOI: 10.58955/jecer.v12i2.119784
|View full text |Cite
|
Sign up to set email alerts
|

Occupational well-being and teamwork in Finnish early childhood education

Abstract: The study examined Finnish early childhood education professionals’ (ECEP) (n = 107) experiences of occupational well-being and systems intelligent teamwork. Occupational well-being was measured with basic psychological job satisfaction, work engagement and burnout. In the analysis of variances by rank, the ECEPs’ had high work engagement, felt competent and relatedness in a working community. By contrast, their autonomy was low, and they felt exhausted, even though the overall burnout level was low. Extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…The narratives showed a contradiction between the expectations of teamwork and organizational practices. Working in Finnish ECEC involves close teamwork and effective discourse (see, e.g., Kumpulainen et al 2023;Ranta & Uusiautti 2022), but our research suggested that not every team is able to work in an environment that fosters teamwork.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…The narratives showed a contradiction between the expectations of teamwork and organizational practices. Working in Finnish ECEC involves close teamwork and effective discourse (see, e.g., Kumpulainen et al 2023;Ranta & Uusiautti 2022), but our research suggested that not every team is able to work in an environment that fosters teamwork.…”
Section: Discussionmentioning
confidence: 70%
“…Teams in Finnish ECEC are diverse, meaning members have different work experience, ways of working and interacting, and expertise based on their various educational backgrounds. While the importance of diversity on ECEC teams has been recognized (Kumpulainen et al 2023;Ranta & Uusiautti 2022), diversity may have negative effects on team performance if members have not spent enough time together (Chatman & Flynn 2001;Williams & Allen 2008). When team members have autonomy, trust each other, and feel safe being themselves, they are motivated to strive toward a common goal, thereby flourishing and driving change (Ranta & Uusiautti 2022;Williams & Allen 2008).…”
Section: Ecec Teamwork and Emotionsmentioning
confidence: 99%
See 3 more Smart Citations